Corrigendum / Erratum / Retraction - Rahmawati, Putri Nur; Anisykurlillah, Indah (Accounting Analysis Journal, 2018)
RETRACTION TO : Putri Nur Rahmawati, Indah Anisykurlillah Title : Factors that Influence the Use of Accounting Information in MSME in Magelang District